Local Wisdom of Kenduri Blang in Acehnese Society: Sociological Analysis of Human Ecology through a Functional Structural Perspective - Nahwa Zainab Marpaung; Rahma Hayati Harahap (TALENTA Publisher, 2024)
Local Wisdom Kenduri Blang is a traditional ceremony of the Acehnese people carried out by descending into the rice fields. The local wisdom of Kenduri Blang has several values and rules that function to maintain and care for the preservation of nature through its plants. The functional structural perspective in this study is used to see the function of the local wisdom of Kenduri Blang in maintaining environmental sustainability carried out by the Acehnese people in Indonesia This research uses a literature study method with secondary data sources, namely books, previous studies, and studies that have been conducted. Data collection techniques are carried out through information collection, research that has been done, and previous studies. Data analysis techniques use a functional structural perspective and an ecological balance paradigm. The results of this study show that there are two customary processes in the local wisdom of Kenduri Blang which shows a good relationship between the people of Aceh and their environment. Local Wisdom Kenduri Blang illustrates this good relationship through traditional processions that oblige people to preserve rice fields before enjoying the harvest.